Relationship of Education with Languages: Policy Perspective of Pakistan from Historical Discourse - Ms. Shereen Gul; Dr. Aqlima Naz; Dr. Adeela Rehman; Ms. Rukhsana Yasmeen (Al-Qanṭara, 2024)
Language is an important factor in social, political, cultural, and economic systems of a country. In the wake of globalization, the role of dominant languages is becoming more visible as the indigenous languages are facing the threat of desertion by their own speakers. Language, at one level, can be viewed as a linking force of communication and at another level a symbol of identity and nationalism. In Pakistan, which is a multilingual country, the issue of language becomes more crucial. It is further complicated as Pakistan has a colonial legacy of English. Thus, the language policy and planning had to deal with the challenges of determining the status of colonial language, national language, and regional languages. Unfortunately, the issue of language did not get much attention in terms of its planning in Pakistan. There is no separate document dealing with the language policy in the country. The education policies, however, would sometime have a section or two on language policy. The only exception to this is a detailed section on language policy in the National Education Commission report (1959). This paper critically examines the language policies reflected in the national Education policies and reports of conferences and commissions; highlighting the gaps between professed policies and actual practices, and reviews the factors responsible for lack of proper implementation of these policies.